MENGUATKAN UKHUWAH DI ERA SOCIETY 5.0: INOVASI PENDIDIKAN MULTIKULTURAL BERBASIS TEKNOLOGI - Ilham, Muhammad Fauzi (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
The Society 5.0 era is characterized by the integration of advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), and big data into daily life to improve human quality of life. In education, this transformation presents both challenges and opportunities to combine technological advancements with humanistic values, particularly in multicultural societies like Indonesia. This article aims to explore how ukhuwah values Islamiyah, insaniyah, and wathaniyah can be strengthened through technology-based multicultural education in the Society 5.0 era. This research employs a library research method, analyzing scholarly literature and reliable sources on technology, multicultural education, and ukhuwah values. The findings indicate that technologies such as Virtual Reality (VR), online learning platforms, and social media can create interactive and collaborative cross-cultural learning experiences. These technologies not only foster tolerance and solidarity but also help students understand and appreciate cultural diversity. However, challenges such as the digital divide, low digital literacy, and cultural homogenization risks must be addressed through comprehensive strategies. These include developing multicultural curricula, providing teacher training, and improving digital literacy. This article provides new insights for educators, policymakers, and academics in creating inclusive, relevant, and ethical education in the Society 5.0 era.